Aplicação de ferramentas BIM em um projeto de cobertura do estádio Professor Dário Rodrigues Leite - Ribeiro, Gabriel do Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In all segments, the companies are looking for the highest productivity with the lowest possible cost, and in the construction industry, the thinking is the same. Over time, techniques that generate more productivity supplanted previous techniques; an example is the CAD technology that replaced free drawings in projects execution. However, the Computer Aided Design (CAD) technology does not deal with certain factors that permeate the entire project. It is required the use of other techniques to supply this need in traditional projects. For example, a software for schedule management, another for assets management and a person who makes calculations for estimates and budgets. The BIM (Building Information Modeling) technology aims to integrate all this information, facilitating the communication among members of a work team and reducing the time required to carry out the project. This work is a applied research, a descriptive research, carried out through modeling and simulation, processes inherent in the use of BIM, a survey was also used only to contextualization. BIM was used for a soccer stadium roof project, in order to verify the feasibility of such use through the analysis of: BIM tools, difficulties encountered and implications of BIM use, and comparison of traditional methods and the use of BIM. To aid the contextualization, a survey was conducted to verify the use of BIM in medium and small companies
Keywords: Industria de construção civil - Automação; Projeto auxiliado por computador; Sistema CAD/CAM; Construction industry